BIMBINGAN ADAB SANTRI PUTRA PONDOK PESANTREN DARUSSALAM BLOKAGUNG KARANGDORO TEGALSARI BANYUWANGI MELALUI KAJIAN KITAB IHYA’ ULUMUDDIN JUZ 1 - Hidayatulloh, Mohammad; mahmudah, mahmudah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This study aims to determine the implementation of guidance on the manners of male students through the study of the book Ihya 'Ulumuddin Juz 1 at the Darussalam Blokagung Islamic Boarding School Karangdoro Tegalsari Banyuwangi. The method used in the adab guidance of male students of the Darussalam Blokagung Islamic Boarding School is by using the method of dhikr, lecture, and discussion or question and answer. The method of studying the book of Ihya' Ulumuddin Juz 1 for male students of the Darussalam Islamic Boarding School is by using the Bandongan method. The adab material in the book of Ihya' Ulumuddin Juz 1 for santri at the Darussalam Blokagung Islamic Boarding School focuses on adab material during the process of seeking knowledge. The results of the analysis show that the application of adab santri contained in the book of Ihya' Ulumuddin Juz 1 at Pondok Pesantren Darussalam Blokagung has entered the good category, although there are still some adab that are still in the process of being applied thoroughly.